2005
DOI: 10.1086/498315
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Tuberculosis among HIV-Infected Patients Receiving Highly Active Antiretroviral Therapy in Europe and North America

Abstract: The level of immunodeficiency at which HAART is initiated and the response to HAART are important determinants of the risk of TB. However, this risk remains appreciable even among those with a good response to HAART, suggesting that other interventions may be needed to control the TB epidemic in the HIV-infected population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(65 citation statements)
references
References 28 publications
2
56
7
Order By: Relevance
“…An additional issue is that we do not know the extent of pathogen-specific CD4+ recovery in tissues upon ART, which appears defective for TB in the lungs even after prolonged viral suppression (20). These considerations may account for the persistently greater susceptibility of successfully treated HIV-infected individuals to TB (65). …”
Section: Discussionmentioning
confidence: 99%
“…An additional issue is that we do not know the extent of pathogen-specific CD4+ recovery in tissues upon ART, which appears defective for TB in the lungs even after prolonged viral suppression (20). These considerations may account for the persistently greater susceptibility of successfully treated HIV-infected individuals to TB (65). …”
Section: Discussionmentioning
confidence: 99%
“…Bakeera-Kitaka et al (2011) reported that the most possible risk factor-low baseline CD4 was not found associated with risk of TB which has the same results with our study. CD4 cell count is not proved to be as a sufficient indicator for TB in HIV-infected children (USCDC, 2009) as in adults (Girardi et al, 2005;Lawn et al, 2011;Sterling et al, 2011), less association has been proved in HIVpositive children till now. Besides, the missing values of CD4 count and percentage may limit our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…5559 These time-dependent changes in TB risk reflect the rate of ART-induced immune recovery, as the absolute current CD4 cell count at any given time during ART is a dominant factor associated with TB risk. 60 A 10-fold reduction in TB risk is observed as CD4 cell counts increase from <100 to >500 cells/μl.…”
Section: Impact Of Antiretroviral Therapymentioning
confidence: 99%